Using the self-etch adhesives in anterior restoration - Tonetto, Mateus Rodrigues [UNESP]; Kabbach, William [UNESP]; Campos, Edson Alves de [UNESP]; Oliveira Junior, Osmir Batista de [UNESP]; Neto, Sizenando de Toledo Porto [UNESP]; Saad, José Roberto Cury [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP] (Jaypee Brothers Medical Publishing, 2012)
With the arrival of self-etch adhesives systems, there has been a rise in interest among clinicians, making it imperative for health professionals to have knowledge of the properties, characteristics, the association as well as the dental structures of these materials, in order to select them and use them correctly. The self-etch adhesive systems show good values of bond strength, microleakage and performance, and have therefore become an option in direct adhesive restorations. In the regard, this case study aims to describe the technique involving the use of selfetch adhesives system for direct restoration of anterior teeth.
Keywords: Esthetics; Restoration; Self-etch adhesives; dentin bonding agent; phosphoric acid; resin cement; adolescent; case report; dental acid etching; dental bonding; dental caries; dental surgery; human; incisor; male; methodology; Acid Etching, Dental; Adolescent; Dental Bonding; Dental Caries; Dental Cavity Preparation; Dental Restoration, Permanent; Dentin-Bonding Agents; Humans; Incisor; Male; Phosphoric Acids; Resin Cements